Analisa Artefak Pada Hasil Radiograf Yang Timbul Akibat Pengolahan Computed Radiography - Wahyuddin Wahyuddin; AR.Rakhmansyah Iskandar; Nurul Adilah Z. (Lontara Journal of Health Science and Technology, 2021)
Artefacts are structures or appearances that are not normally present on radiographs, errors in radiographic processing may be due to technical errors or film processing errors. This research was conducted using Descriptive methods, with the type of literature study that aims to examine the causes of artifacts that can occur as a result of improper handling of film processing errors.The results of the analysis concluded that the frequent occurrence of artifacts in the processing of Computed Radiography is caused by two factors, that is the use of imaging plates and grids lisolm. His advice should be in the processing using Computed Radigraphy the officer must be more careful and pay attention to the components in Computed Radiography.